2011
DOI: 10.1016/j.cbi.2011.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Human and rodent aldo–keto reductases from the AKR1B subfamily and their specificity with retinaldehyde

Abstract: NADP(H)-dependent cytosolic aldo-keto reductases (AKR) are mostly monomeric enzymes which fold into a typical (α/β)8-barrel structure. Substrate specificity and inhibitor selectivity are determined by interaction with residues located in three highly variable loops (A, B, and C). Based on sequence identity, AKR have been grouped into families, namely AKR1–AKR15, containing multiple subfamilies. Two human enzymes from the AKR1B subfamily (AKR1B1 and AKR1B10) are of special interest. AKR1B1 (aldose reductase) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 38 publications
(48 reference statements)
2
33
0
Order By: Relevance
“…Specifically, both PCN and TCPOBOP markedly up-regulated multiple glutathione S -transferases, which are important for glutathione conjugation of substrates and chemical detoxification (Parkinson et al, 2013). Regarding retinoid metabolism, both PCN and TCPOBOP markedly up-regulated Akr1b7, which is important in the metabolism of retinaldehyde (Ruiz et al, 2011) and the detoxification of lipid peroxidation byproducts (Liu et al, 2009); PCN and TCPOBOP also up-regulated Cyp26a1, which is important in the elimination of active retinoids (Topletz et al, 2015). In addition, Abcd2, which is an Abc transporter of which the promoter activity of is induced by 9-cis-retinoic acid (Pujol et al, 2000), was up-regulated by PCN and TCPOBOP.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, both PCN and TCPOBOP markedly up-regulated multiple glutathione S -transferases, which are important for glutathione conjugation of substrates and chemical detoxification (Parkinson et al, 2013). Regarding retinoid metabolism, both PCN and TCPOBOP markedly up-regulated Akr1b7, which is important in the metabolism of retinaldehyde (Ruiz et al, 2011) and the detoxification of lipid peroxidation byproducts (Liu et al, 2009); PCN and TCPOBOP also up-regulated Cyp26a1, which is important in the elimination of active retinoids (Topletz et al, 2015). In addition, Abcd2, which is an Abc transporter of which the promoter activity of is induced by 9-cis-retinoic acid (Pujol et al, 2000), was up-regulated by PCN and TCPOBOP.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, a region located between amino acid residues 80 and 100, showing high sequence differences and forming an α-helix and a turn, is found to be located close to the conserved catalytic residue Lys78. As noted by Ruiz et al [6], all the human and murine proteins of the aldose reductase type (AKR1B1, AKR1B3 and AKR1B4) share a common Leu125, whereas all the other enzymes share a common Lys125, with the exception of AKR1B16 and AKR1B17 having a Thr at that position. A Lys at position 125 appeared to be an important determinant for all-trans-retinaldehyde specificity of AKR1B10 [43].…”
Section: Sequence Alignmentmentioning
confidence: 83%
“…It is expressed in numerous tissues and a recent study determined a 20-fold prevalence in brain as compared to other tissues [1]. AKR1B3 acts as an aldose reductase, showing a similar K m value for glucose (82 mM [13]) and catalytic efficiency with D,Lglyceraldehyde as the human ortholog AKR1B1, and also exhibits low activity with retinaldehyde [6]. Mouse AKR1B3 has been widely studied in in vivo models due to the crucial role of human AKR1B1 in the development of diabetic complications [17].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…AKR1B10 is also active to alltrans-retinal, a precursor of the signaling molecule retinoic acid that regulates cell proliferation and differentiation, and to polycyclic aromatic hydrocarbon, an environmental procarcinogen [7][8][9][10][11][12]. Recent studies from our and other laboratories have shown that AKR1B10 can reduce the C-13 ketonic group in daunorubicin and idarubicin, leading to chemoresistance of cancer cells to these cytostatic agents [13][14][15], suggesting that AKR1B10 is an important carbonyl reductase involved in cell growth and proliferation and in drug resistance.…”
Section: Introductionmentioning
confidence: 99%